International climate adaptation assistance: Assessing public support in Switzerland - Liliana Andonova; Agnese Zucca; Simon Montfort; Nives Dolšak; Aseem Prakash (PLoS ONE, 2025)
Lower-income countries account for a small share of accumulated greenhouse gas emissions but are highly vulnerable to climate-induced events. In response, industrialized higher-income countries, the major contributors to greenhouse gas stock, have pledged policy packages to support developing countries to adapt to climate change. Foreign aid and international migration often figure prominently in such packages. We employ a survey-embedded conjoint experiment to assess public support in Switzerland for international climate assistance packages which consist of six attributes: (1) the country receiving the package (Algeria, Kenya, Bangladesh, and the Philippines); (2) the volume of Swiss bilateral climate aid to this country; (3) the number of climate migrants from this country in Switzerland; (4) types of extreme weather event this country faces; (5) Swiss trade with this country; and (6) the country’s record of voting with Switzerland in the United Nations Security Council. We find that while Swiss respondents are indifferent to aid volume, their support for the policy package diminishes as the number of migrants increases. Respondents support policy packages for countries that trade with and vote alongside Switzerland in the Security Council. Respondents also have country-specific preferences: they support assistance to the Philippines, disfavor Algeria, and are indifferent to Kenya and Bangladesh. Ideology, cultural beliefs, and benchmarking with peer countries of Global North or past Swiss aid and immigration records do not change support for the policy package.